Policy-based management for resource-specific semantic service - KEENEY, JOHN; LEWIS, DAVID; O'SULLIVAN, DECLAN (IEEE, 2006)
Semantic Web Services are the subject of intense scrutiny as they promise to address problems of dynamically discovering, selecting, composing and interoperating web services for e-commerce. However, there has been relatively little attention paid to the application of semantic service models to non-web services. Services in telecommunications and enterprise networks can equally be modeled as individual or composed semantic services, but with alternative grounding to the underlying, domain-specific service mechanisms. These domains reveal a further interesting requirement for the modeling of semantic services in that they often represent services on specific devices. As these devices house resources that must be managed as part of the operation of the network, the semantic model of the service must be integrated with the model that allows the resources to be efficiently managed. This paper presents a scheme via which policy-based management directives for a resource can be applied to a device offering semantically annotated services. We show that this integration can be achieved using existing service choreography expressions and illustrate this using an enterprise networking example based on existing standardized semantics for networked printers.
PUBLISHED
Keywords: Computer Science